A New Deal for OLMC’s? Three Challenges - Kymlicka, Will (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2012)
While Canada is widely seen as a leader in accommodating different forms of diversity, the unique needs of official language minority communities (OLMCs) are not adequately recognized in the constitution, and often fall through the cracks of the “Canadian model”. Can we imagine a new deal for OLMCs, perhaps in the form of new legislation or even a new constitutional provision that would provide stronger recognition of their national status, their collective rights, and their political autonomy? While I share the political objectives of achieving greater recognition and autonomy, this paper identifies a number of potential pitfalls and dead-ends that need to be avoided in the pursuit of such a new deal. I focus in particular on a) the role of legal categories, b) the limits of international law, and c) the constraints on constitutional reform.